The vehicle braking systems as main source of inhalable airborne magnetite particles in trafficked areas. (January 2022) - Ingo, Gabriel M.; Riccucci, Cristina; Pisani, Gianluca; Pascucci, Marianna; D'Ercole, Daniele; Guerriero, Ettore; Boccaccini, Francesca; Falso, Giacomo; Zambonini, Gianpaolo; Paolini, Valerio; Di Carlo, Gabriella
Graphical abstract: Abstract: Magnetite (Fe3 O4 ) nano-particles (M NPs) have been found in human tissues and causally linked to serious illnesses. The possible negative role of MNPs has been not still fully ascertained even though MNPs might cause health effects due to their magnetic property, redox activity and surface charge. The origin of MNPs in human tissues still remains to be unambiguously identified since biological processes, natural phenomena and anthropogenic production have been proposed. According to this latter increasingly convincing hypothesis, anthropogenic MNPs might enter mainly in the human body via inhalation, penetrate deeply into the lungs and in the alveoli and also migrate into the blood circulation and gather in the extrapulmonary organs and central nervous system. In order to identify the releasing source of the potentially inhalable MNPs, we pioneered an innovative approach to rapidly investigate elemental profile and morphology of a large number of airborne micron and sub-micron-sized Fe-bearing particles (FePs). The study was performed by collecting a large amount of micron and sub-micron sized inhalable airborne FePs in trafficked and densely frequented areas of Rome (Italy). Then, we have investigated individually the elemental profile and morphology of the collected particles by means of high-spatial resolution scanning electron microscopy, energy dispersive spectroscopy and an automated software purposely developed for the metal-bearing particles analysis. On the basis of specific elemental tracing features, the investigation reveals that almost the total amount of the airborne FePs is released by the vehicle braking systems mainly in the form of magnetite. Furthermore, we point out that our approach might be more generally used to identify the releasing sources of different inorganic airborne particles and to contribute to establish more accurately the impact of specific natural or anthropogenic particles on the environment and human health.